GAMBARAN PERAWATAN KAKI PADA PENDERITA DIABETES MELLITUS DI PUSKESMAS - aastihar (Media Husada Journal Of Nursing Science, 2024)
Diabetes mellitus is a metabolic disorder characterized by increased blood glucose levels. Data from the World Health Organization (WHO) shows an increase in the number of diabetes mellitus sufferers throughout the world, with a risk of death from this disease, especially in countries with low and middle economic status. In the Southeast Asia region, including Indonesia, the prevalence rate of diabetes mellitus is also quite high. This research was conducted to carry out foot care practices for diabetes mellitus sufferers at the Muara Bulian Community Health Center, Batanghari Regency, in 2023. Research Method: This research uses a quantitative research design with descriptive methods. The research sample was selected using a purposive sampling technique, and the number of samples taken was 83 respondents. Results and Discussion: The results of the study showed that the majority of respondents were early elderly (46-55 years), female, had primary education, and had suffered from diabetes mellitus for less than five years. Most respondents had never received education about foot care, and most of them performed foot care in the poor category. This shows a lack of knowledge and good foot care practices in diabetes mellitus sufferers.